Adhesion molecules as diagnostic and severity biomarkers in pediatric community-acquired pneumonia - Tanir Basaranoglu, Sevgen; Ozsurekci, Yasemin; Aykac, Kubra; Iyigun, Irem; Satirer, Ozlem; Akin, Mustafa Senol; Ceyhan, Mehmet (Wiley, 2021)
Background Discrimination of the cases with severe and mild pneumonia is crucial due to the requirement of hospitalization, additional management, and treatment protocols. We aimed to analyze the role of IL6 (Interleukin), IL8, IL10, VCAM-1 (soluble Vascular Cell Adhesion Molecule), and sSELE (soluble E-selectin) in the diagnosis and prognostic evaluation of community-acquired pneumonia (CAP). Methods Pediatric patients with severe pneumonia (SP) were hospitalized and patients with mild disease (MP) were treated in the community. IL6, IL8, IL10, VCAM-1, and sSELE levels of the patients were investigated and compared with the age- and gender-matched healthy subjects. Results A total of 113 patients fulfilling the criteria for a diagnosis of CAP were enrolled in the study, 62 (54.8%) of which had SP and 51 (45%) had MP. MP and SP groups were significantly different in terms of IL8, IL10, and sSELE levels. Patients with SP and MP had significantly different WBC, ESR, and CRP values, as well. Conclusions Besides classical acute phase parameters, inflammatory response parameters such as IL6 and VCAM-1 levels may be helpful in diagnosis of pneumonia. In terms of determination of disease severity in pediatric CAP, systemic inflammatory markers like IL8 and IL10 and adhesion molecules like sSELE seem useful in clinical settings.
Keywords: adhesion molecules; community? acquired pneumonia; diagnosis of pneumonia; pediatric